Carboxylic bacterial cellulose fiber-based hydrogel electrolyte with imidazole-type ionic liquid for dendrite-free zinc metal batteries - Zhang, Tianyun; Shi, Xiaohong; Li, Yu; Sangaraju, Sambasivam; Wang, Fujuan; Yang, Liang; Ran, Fen (Materials Reports: Energy, 2024)
Aqueous zinc metal batteries are regarded as the most promising energy storage system due to their advantages of high safety, low cost, and high theoretical capacity. However, the growth of dendrites and the occurrence of side reactions hinder the development of zinc metal batteries. Despite previous attempts to design advanced hydrogel electrolytes, achieving high mechanical performance and ionic conductivity of hydrogel electrolytes has remained challenging. In this work, a hydrogel electrolyte with an ionic crosslinked network is prepared by carboxylic bacterial cellulose fiber and imidazole-type ionic liquid, following by a covalent network of polyacrylamide. The hydrogel electrolyte possesses a superior ionic conductivity of 43.76 mS cm−1, leading to a Zn2+ migration number of 0.45, and high mechanical performance with an elastic modulus of 3.48 GPa and an elongation at breaking of 38.36%. More importantly, under the anion-coordination effect of the carboxyl group in bacterial cellulose and [BF4]− in imidazole-type ionic liquid, the solvation sheath of hydrated Zn2+ ions and the nucleation overpotential of Zn plating are regulated. The results of cycled testing show that the growth of zinc dendrites is effectively inhibited and the generation of irreversible by-products is reduced. With the carboxylic bacterial cellulose-based hydrogel electrolyte, the Zn||Zn symmetric batteries offer good cyclability as well as Zn||Ti batteries. [Display omitted]